If we plug the x and y values of each of the given coordinate points into the right equation, we should get two valid statements:
f. 5 = -12(-3) - 32 ⇒ 5 = 36 - 32 ⇒ 5 ≠ 4
-3 = -12(1) - 32 ⇒ -3 = -12 - 32 ⇒ -3 ≠ -44
g. 5 = -(-3) + 2 ⇒ 5 = 3 + 2 ⇒ 5 = 5
-3 = -1 + 2 ⇒ -3 ≠ 1
h. 5 = -2(-3) - 1 ⇒ 5 = 6 - 1 ⇒ 5 = 5
-3 = -2(1) - 1 ⇒ -3 = -2 - 1 ⇒ -3 = -3
The equation y = -2x - 1 contains the points (-3, 5) and (1, -3). I didn't check the last one because I got the right answer before getting to it, but let me know if you want me to show the check.